Implementasi Pembelajaran Berdiferensiasi pada Mata Pelajaran PPKn dalam Mewujudkan Merdeka Belajar di SMP Labschool Jakarta - Ramadhan, Abhi Rachma; Afif; Chaerani, Annisa; Hazmin Hafid Putranto (Universitas Pendidikan Ganesha, 2025)
The low fulfillment of learning needs is an obstacle for students, as students have diverse characteristics that must be met. This makes it an important aspect of Civics learning to meet the needs of students through Differentiated Learning. Differentiated learning can meet the needs of students to understand learning material based on their ability to suit their interests and talents. This study aims to see the results of differentiated learning in implementing the embodiment of the independent curriculum in Civics subjects held in class IX-A at SMP Labschool Jakarta as the research subject. Then the approach taken is qualitative, coupled with a descriptive analysis method. Meanwhile, data collection techniques were carried out by observing the field, interviewing informants, and documenting results during implementation. The results obtained after implementing differentiated learning are that it is suitable for practice in the classroom environment at school as part of accommodating the learning needs of heterogeneous students so that it is hoped that students can develop their learning activities optimally.